2020
DOI: 10.3892/or.2020.7520
|View full text |Cite|
|
Sign up to set email alerts
|

PLCε knockdown enhances the radiosensitivity of castration‑resistant prostate cancer via the AR/PARP1/DNA‑PKcs axis

Abstract: Radiotherapy (RT) has been used as a therapeutic option for treatment of prostate cancer (PCa) for a number of years; however, patients frequently develop RT resistance, particularly in castration-resistant PCa (CRPC), although the underlying mechanisms remain unknown. Understanding the underlying mechanism of RT resistance in CRPC may potentially highlight novel targets to improve therapeutic options for patients with PCa. In the present study, the expression levels of phospholipase Cε (PLCε), androgen recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The dysregulation of the DNA-PKcs has been implicated in PC progression, metastasis, and resistance to therapy, and its upregulation correlates with poor patient outcomes [60,137,138]. In a study by Pu J. et al, it was suggested that the downregulation of the Androgen receptor/PARP/DNA-PKcs axis could be used as a potential therapeutic strategy to increase the radiosensitivity of castrate-resistant PCs [139].…”
Section: Dna-dependent Protein Kinase Catalytic Subunit (Dna-pkcs)mentioning
confidence: 99%
“…The dysregulation of the DNA-PKcs has been implicated in PC progression, metastasis, and resistance to therapy, and its upregulation correlates with poor patient outcomes [60,137,138]. In a study by Pu J. et al, it was suggested that the downregulation of the Androgen receptor/PARP/DNA-PKcs axis could be used as a potential therapeutic strategy to increase the radiosensitivity of castrate-resistant PCs [139].…”
Section: Dna-dependent Protein Kinase Catalytic Subunit (Dna-pkcs)mentioning
confidence: 99%
“…In early stage, when the disease is limited to the prostate, surgical and/or medical castration is the most preferred therapy, but more than 90% of patients develop castration-resistant prostate cancer (CRPC) ( 1 ). Although, radiotherapy is an alternative therapeutic choice for patients with CRPC ( 3 ), the relapse presented following radiation therapy in 30–50% patients still ( 4 , 5 ).One new and very effective strategy involves the administration of radio-ligands that target prostate-specific membrane antigen (PSMA), which is overexpressed in prostate cancer cells. For this purpose, both the beta-emitter Lu-177 and the alpha-emitter Ac-225 are coupled to PSMA-617 or PSMA-I&T targeting metastatic prostate cancer cells ( 6 , 7 ).However, these therapies are not promoted by the China Food and Drug Administration (CFDA).…”
Section: Introductionmentioning
confidence: 99%